2009
DOI: 10.1021/es900411k
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Biotransformation of Polybrominated Diphenyl Ethers (PBDEs) by Bacterial Isolates

Abstract: Polybrominated diphenyl ethers (PBDEs) are flame retardants that have been used in consumer products and furniture for three decades. Currently, very little is known about their fate in the environment and specifically about their susceptibility to aerobic biotransformation. Here, we investigated the ability of the polychlorinated biphenyl (PCB) degrading bacteria Rhodococcus jostii RHA1 and Burkholderia xenovorans LB400 to transform mono- through hexa-BDEs at ppb levels. We also tested the PBDE transforming a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(65 citation statements)
references
References 43 publications
6
58
1
Order By: Relevance
“…It was reported that strain RHA1 was able to release large amounts of bromide ions during the transformation of tetrabromodiphenyl ether (PBDE-47) (Robrock et al, 2009). And strain DB-1 debrominated part of PBDE-209 at aerobic incubation using lactate as carbon source (Deng et al, 2011).…”
Section: Presence and Formation Of Br àmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that strain RHA1 was able to release large amounts of bromide ions during the transformation of tetrabromodiphenyl ether (PBDE-47) (Robrock et al, 2009). And strain DB-1 debrominated part of PBDE-209 at aerobic incubation using lactate as carbon source (Deng et al, 2011).…”
Section: Presence and Formation Of Br àmentioning
confidence: 99%
“…PH-07 could aerobically break down a number of lower-bromodiphenyl ethers congeners, such as mono-, di-, and tribromodiphenyl ethers. In recent years, Robrock et al (2008Robrock et al ( , 2009) investigated four strains which could transform mono-through hexabromodiphenyl ethers at ppb level. In these studies, two PCB-degrading strains, Rhodococcus jostii RHA1 and Burkholderia xenovorans LB400 transformed all of the mono-and pentabromodiphenyl ethers and strain LB400 transformed one of the hexabromodiphenyl ethers, while Rhodococcus sp.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rhodococcus sp. RR1 could aerobically transform 20% of 17 ug L -1 mono-and di-BDE within three days [23]. Sphingomonas sp.…”
Section: -Bde Removal Efficiencymentioning
confidence: 99%
“…Microbial anaerobic transformation has demonstrated that, in most cases, PBDEs were debrominated to less brominated congeners, but required a relatively long time [11,22]. Compared to anaerobic degradation, the advantages of microbial aerobic degradation on PBDEs are obvious: the degradation time cycle is shorter and the metabolites will not carry greater toxicity as the result of the characteristic degradation mechanism that PBDEs go through for hydroxylation and ring opening reaction [23][24].…”
mentioning
confidence: 99%
“…Three PBDE technical mixtures [pentabromodiphenyl ether,octabromodiphenyl ether and decabromodiphenyl ether (BDE 209)] were widely integrated into products. As of 2006, the penta-and octa-bromodiphenyl ether technical mixtures have been banned and removed from production (Robrock et al 2009). However, BDE 209 remains legal in most countries and continues to be heavily used (He et al 2006).…”
Section: Introductionmentioning
confidence: 99%